Williama Goldinga Siłą bezwładu w perspektywie ontologii zorientowanej na przedmiot - Kowalcze, Małgorzata (Przestrzenie Teorii, 2021)
The paper applies selected devices of the methodology of Object-Oriented Ontology to study William Golding’s novel Free Fall. Particular attention is given to Graham Harman’s project, whose definition of an object accounts for all beings, humans included. Within the ontological structure of an object two components can be distinguished: the “sensual object”, which can engage in relationships with other objects, and the “real object”, which refrains from any connections. The author aims to show how the main protagonist of Golding’s novel is impacted on by material objects, how other humans are perceived by him as inherently dual beings, but most importantly how the protagonist himself discovers the thing-like quality of his own human condition.